Impact of Nutritional Intervention for Patient with Cerebrovascular Accident and Atrial Fibrillation Secondary to Hypertensive Emergency - Roslan, Noor Izati; Ahmad Zamuri, Aina Nadhra; Ab. Hamid, Mohd Ramadan; binti Baharudin, Nurul Nurliana (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This case study aims to report on the nutrition management of Cerebrovascular Accidents (CVA) which have a higher risk of malnutrition due to dysphagia, hemiparesis, decreased mobility, and dementia. Mrs. L, a 76-year-old Chinese lady, was less responsive at home. Upon admission, she was diagnosed with hypertensive emergency complicated by CVA, newly diagnosed atrial fibrillation, and End-Stage Renal Disease (ESRD). Her Body Mass Index (BMI) is 22.5 kg/m2, which is underweight for her age. The patient, with abnormal blood results, high blood pressure, and poor Glasgow Coma Scale (GCS) score, was treated with nasogastric enteral feeding and a disease-specific formula for diabetes. Inadequate enteral nutrition infusion related to feeding has yet to optimize as evidenced by intake of 57% of energy and 0.6 g/kg body weight of protein. Mrs. L required 1,442 kcal of energy and 57.7 g of protein (1 g/kg body weight) to meet adequate bodily function and prevent further weight loss. The nasogastric enteral feeding was optimized to 250 mL, seven times daily using the same diabetic formula. Throughout follow ups, although the patient’s dietary intake improved, she experienced episodes of diarrhea. She was also put on a 500 mL fluid restriction per day. Considering those issues, the diseasespecific formula was changed to renal disease formula. The patient then progressed to a soft diet with improved GCS scores and other conditions. This case highlights dysphagia which is the leading cause of malnutrition in stroke patients, associated with poor prognosis, increased mortality, and deteriorated health outcomes, necessitating enteral nutrition support to enhance nutritional status and promote health. It can be concluded that MNT in managing patients with CVA, hypertensive emergency, and underlying diseases of diabetes and ESRD helps to improve the patient’s recovery. The patient's treatment and diet should be optimally adjusted through close monitoring and evaluation